THE RELATIONSHIP BETWEEN CIRCADIAN RHYTHM AND OBESITY IN SHIFT-WORKERS (Third Sector Social Economic Review, 2020)
Night workers are needed to ensure continuity in production with developing technology. While the shift system provides continuity in production, it is an advantage; It is a health problem for individuals who work contrary to their daily routines. This irregularity in the circadian rhythm (CR), also known as the biological clock, causes many chronic health problems in individuals. Obesity, one of the biggest problems of developed and developing societies, is one of these problems. Obesity; It is a risk factor for serious diseases such as hypertension, cardiovascular diseases, stroke and cancer. Therefore, protection against obesity will be ensured against larger problems. Individuals working in shifts are affected by the irregularity of the CR and the frequency of obesity increases rapidly in employees.  This review article was prepared to show the relationship between obesity and the reason that the shift system causes irregularity in the CR.
Keywords: Shift-Work; Circadian Rhythm; Obesity